2003
DOI: 10.1116/1.1621652
|View full text |Cite
|
Sign up to set email alerts
|

n -type doping characteristics of O-implanted GaN

Abstract: Dissociation of Al 2 O 3 (0001) substrates and the roles of silicon and oxygen in n-type GaN thin solid films grown by gas-source molecular beam epitaxy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Figure 7a shows the influence of different ICP power treatments on ohmic contact at an RF power of 75 W. As ICP power increases from 150 W to 250 W, R C decreases slightly. According to the literature [34], the majority of the implanted O ions were present at an interstitial site in GaN, and consequently had not contributed to the formation of the O donor level. Therefore, excluding the donor-doping effect of O N introduced by oxygen plasma treatment, and there may be other mechanisms to reduce R C .…”
Section: Algan/gan Hemts DC Characteristicsmentioning
confidence: 99%
“…Figure 7a shows the influence of different ICP power treatments on ohmic contact at an RF power of 75 W. As ICP power increases from 150 W to 250 W, R C decreases slightly. According to the literature [34], the majority of the implanted O ions were present at an interstitial site in GaN, and consequently had not contributed to the formation of the O donor level. Therefore, excluding the donor-doping effect of O N introduced by oxygen plasma treatment, and there may be other mechanisms to reduce R C .…”
Section: Algan/gan Hemts DC Characteristicsmentioning
confidence: 99%
“…Unbound oxygen can diffuse into the defective material near the GaN/Al2O3 interface, changing its electrical properties [239]. However, the oxygen redistribution in O implanted GaN is not observed up to the temperature of 1200 • C [238,240]. Subsequent studies have shown that due to the high activation energy of oxygen diffusion in GaN ∼ 3.9 eV, the incorporated oxygen atoms exhibits low mobility even at the temperatures close to the melting point of the material [241].…”
Section: Oxygen Properties In Ganmentioning
confidence: 99%
“…9 Furthermore, we have demonstrated that improved Ge-doping characteristics in GaN have been achieved by N/Ge coimplantation for n-type doping, attaining activation efficiencies above 95%, compared with those of the conventional Ge implantation where only Ge dopant is used. 10 However, defects introduced by the Ge and/or N/Ge implantation have not yet been studied in detail. In general, implantationinduced defects limit the performance of the electronic devices.…”
Section: Defects In Nõge Coimplanted Gan Studied By Positron Annihilamentioning
confidence: 99%
“…For the conventional Ge-implanted GaN sample, the activation efficiencies were roughly estimated to be as low as 40% because of there being insufficient N atoms to maintain the GaN stoichiometry in the implanted region. 9,10 For the VEPAS measurements, using a monoenergetic positron beam, the Doppler broadening of the electronpositron annihilation ␥ rays ͑ϳ511 keV͒ was recorded at room temperature with a Ge detector as a function of incident positron energy E. A spectrum was measured for each value of E. The shape of the Doppler broadening spectrum was characterized by the conventional low and high electron momentum parameters S and W. 15 the Doppler broadening of the resultant annihilation ␥ rays. Therefore the level of the Doppler broadening is a measure of the momentum state of the electron that a positron annihilates.…”
Section: Defects In Nõge Coimplanted Gan Studied By Positron Annihilamentioning
confidence: 99%